Age and body stature, handgrip, and strength endurance analyses of elite weightlifters: boosting 1RM bench press - Uchenna K. Ezemagu; Godwin C. Uzomba; Amarachi E. Okoro; A.O. Ibegbu (Universidade Estadual Paulista (UNESP), 2022)
Abstract Aim: This study aims to characterize the body stature and age, handgrip, and endurance strength of elite male weightlifters, and ascertain the anthropometric features that can boost IRM bench press. Methods: Forty-four elite male weightlifters of different weight categories participated in this study. All participants were members of the Ebonyi state team in Nigeria. We assessed their body weight, height, arm span, arm girth, chest girth, hip girth, thigh girth, handgrip strength, 1RM, time for repetitions (TR), and the number of repetitions (NR) of bench press, using National Strength and Conditioning Association's guidelines. Results: 1RM bench press depends on waist and thigh girths, while the speed of bench press was associated with height and arm span of elite weightlifters. 1RM, NR, and TR of bench press depend on age, body weight, and BMI. Consistently, NR of bench press increase with age; range 18, 22 years, and body weight increases with age; range 28, 32 years, while handgrip strength reduces with age; range 38 years and above (p < 0.05). Conclusion: The strength of association of age, and BMI with strength endurance and 1RM bench press was robust and similar, but inconsistent with handgrip strength. It also suggests that enhancing the musculoskeletal structures of the thigh and waist could boost 1RM bench press while handgrip strength could not but reduces as age advances beyond 38 years.